Patients' preferences for distributing limited government-funded IVF cycles - Jones, Claire Ann (Bioethics, 2022)
Objective On December 21, 2015, Ontario began funding one cycle of IVF for each resident with a uterus under the age of 43, but with a program cap that is insufficient to meet the annual demand. Our objective was to determine how fertility patients believe that the limited number of funded IVF cycles should be distributed. Methods A survey was distributed to patients attending a university affiliated hospital-based fertility clinic in downtown Toronto, including its associated peripheral satellite clinics. Results From August 2016 to March 2017, 271 patients responded to the survey, of whom 90.3% were in favour of public funding for IVF. The majority of participants favoured allocating IVF cycles to maximize patients’ access to IVF in Ontario rather than targeting funded IVF cycles so as to maximize live births (62.7% vs. 32.8%). Most participants wanted all clinics to adopt the same approach for distributing funded IVF cycles compared to the current system in which each clinic chooses its own criteria for allocation (84.5% vs. 8.5%). Participants favoured distributing IVF by way of a scoring system that took individual patient factors into account. However, the factors that each respondent considered important varied materially. Conclusion Patients overwhelmingly supported public funding for IVF, desired a consistent policy for distribution of limited funded IVF cycles at all clinics, and preferred a method that took individual patient factors into consideration when determining patient priority for funded IVF but there were heterogenous opinions on which factors should be included.